A SYSTEMATIC REVIEW OF PAKISTANI PUBLIC PERCEPTION TOWARDS MENTAL ILLNESS - Sajid Nawaz; Zuhair Manzoor; Rabia Basri; Ahmad Ali; Shumaila Afzal; Abid Hussain; Humna Aroob; Niaz Hussain (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
Objective: This study investigates how the Pakistani community views mental health issues by reviewing scientific material from several databases. The findings are expected to benefit the general public, clinicians, and researchers. Methodology: This literature review selected and analyzed papers that looked into how the Pakistani population views and understands mental health concerns. We searched important databases like Cochrane and Google Scholar. Researchers investigated Pakistani participants' mental health attitudes and understandings using scientific methods. Reading the selected publications and tabulating the findings resulted in data extraction. Results: The results of these studies were analyzed. According to the findings, Pakistanis have little to no concept of their psychological and emotional processes as distinct entities. Religion and mythical or supernatural understandings are two of the sociocultural concepts discussed in this study that are similar. Mental disorders are treated with drugs. Pakistanis have a limited understanding of psychological and emotional experiences as well as a limited vocabulary. The community's reactions to mental health issues are influenced by social, cultural, and religious elements. The community has its own ideas and beliefs about what causes diseases, how to keep them from happening, and how to treat them.